IT Governance in the e-Business Era - Saida Harguem; Karim Ben Boubaker; Imen Ameur (International Journal of Management and Data Analytics)
In the context of e-businesses, Information Technologies (IT) are not only simple support to companies' businesses, but they often constitute an integral part of their main activities. IT Governance practices are also evolving to fulfill the e-business environment's requirements. A conceptual framework is developed through a literature review, presenting a synthesis of various dimensions (structure, processes, and mechanisms) structuring IT Governance in the era of the e-business.